Ecoprint Steaming Technique for Interactive and Eco-Friendly Learning Among Primary Teachers at SD Gugus Dham Lubuk - Cut Mawar Helmanda; Meutia Zahara; Nazariah; Siti Salsabila; Ilham Wahyudi; Ori Resmida (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
This community engagement project addresses the limited use of interactive, environmentally friendly teaching methods in primary education, particularly among teachers at SD Gugus Dham Lubuk, Aceh Besar. The study aimed to introduce and train teachers using the ecoprint steaming technique as an innovative learning approach that integrates environmental sustainability with hands-on art-based activities. The program followed a structured process of socialization, training, classroom application, and mentoring, involving 30 teachers in demonstrations and practice using natural materials such as leaves and flowers. Before the training, 85% of teachers had never been exposed to ecoprint and still relied on lecture-based methods that limited creativity and engagement. Post-training results indicated increased teacher participation, creativity in lesson planning, and readiness to apply ecoprint in classrooms. Teachers successfully integrated the method into science and art lessons, enhancing student engagement while fostering environmental awareness. Beyond these immediate outcomes, sustainability measures were established through digital modules, a class “ecoprint corner”, and continuous mentoring with local stakeholders. These efforts ensure long-term adoption of interactive, eco-friendly teaching practices. Furthermore, the initiative demonstrated the potential for sustainable creative economy activities, as teachers and students produced marketable products showcased in a school exhibition, linking education with environmental stewardship and local economic empowerment.